Pengaruh Desain Interior terhadap Kenyamanan Pengguna di Perpustakaan UIN Ar-Raniry Banda Aceh - Muhammad Naufal; Nisa Putri Rachmadani; Mira Alfitri (Bayt ElHikmah: Journal of Islamic Architecture and Locality, 2023)
The college library is a place for students to be used as a science-based recreation area. To fulfill this, a comfort is needed for visitors, especially students, to feel at home and feel / want to continue to linger while in the library. Wicaksana (2016) defines comfort as a relaxed condition, where pain is not felt between all limbs. Factors from the interior of the library also greatly influence students to feel more comfortable when they are in the room in the library.